Ecologically based management of rodents in lowland irrigated rice fields in Indonesia - Jacob, Jens; Sudarmaji; Singleton, Grant R.; Rahmini; Herawati, Nur A.; Brown, Peter R. (Commonwealth Scientific and Industrial Research Organisation, 2010)
Context. Overabundant rodents cause considerable crop damage and, in developing countries of South-east Asia, rodents can be an obstacle to attempts at alleviating poverty. Management is often based on the use of chemicals that can harm non-target species. Therefore, an effective and environmentally benign management approach such as ecologically based rodent management (EBRM) is desirable. Aims. We compared the effectiveness of EBRM to that of conventional management on populations of rice-field rats (Rattus argentiventer). Methods. The study was conducted as a large-scale replicated field trial in lowland irrigated rice fields in West Java, Indonesia. EBRM actions included habitat manipulations, removal of rats with trap barrier systems, coordinated rat-control campaigns and synchrony of cropping on the village level. We measured abundance, population structure, and breeding of rice-field rats as well as rice production and crop damage caused by rats. Key results.Although there was no overall effect of the EBRM treatment on rat abundance, we found decreasing rat abundance in rice-field habitats at the late cropping stage in treated villages and a decrease in body size of rats. In addition, we found fewer reproducing females when EBRM was applied than with the application of conventional methods, whereas male reproductive condition did not decrease. Overall, there was a reduction in mean crop damage when EBRM was applied (4.4 ± 0.4% in treatments v. 2.5 ± 0.4% in experimental controls), which translated into 6% higher rice production. Conclusions. The results demonstrated that EBRM is an appropriate approach to manage overabundant rodents in irrigated lowland rice-based agro-ecosystems and possibly in other agro-ecosystems. This will provide substantial benefits for smallholder farming communities in developing countries and most likely benefits for ecosystem health. Implications. The EBRM approach should be used routinely in irrigated lowland rice crops that are at risk of damage by rice-field rats.